2015
DOI: 10.3174/ajnr.a4474
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Tumor Progression from Pseudoprogression in Patients with Glioblastomas Using Diffusion Tensor Imaging and Dynamic Susceptibility Contrast MRI

Abstract: BACKGROUND AND PURPOSE:Early assessment of treatment response is critical in patients with glioblastomas. A combination of DTI and DSC perfusion imaging parameters was evaluated to distinguish glioblastomas with true progression from mixed response and pseudoprogression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
118
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(121 citation statements)
references
References 32 publications
3
118
0
Order By: Relevance
“…In comparison to further studies that assessed the diagnostic potential for differentiation of PsP and PD, the results of the current study might be more promising than studies evaluating diffusion tensor imaging, dynamic susceptibility contrast and quantitative dynamic contrast-enhanced MRI [38,39]. On the other hand we received less promising results than recently published data by Galldiks et al for PET [40].…”
Section: Discussionmentioning
confidence: 60%
“…In comparison to further studies that assessed the diagnostic potential for differentiation of PsP and PD, the results of the current study might be more promising than studies evaluating diffusion tensor imaging, dynamic susceptibility contrast and quantitative dynamic contrast-enhanced MRI [38,39]. On the other hand we received less promising results than recently published data by Galldiks et al for PET [40].…”
Section: Discussionmentioning
confidence: 60%
“…37 Thus the totality of the evidence indicates that DSCis fairly accurate in identifying true tumor progression. Achieving even greater accuracy may require combining DSC data with other advanced imaging modalities such as DTI, 38 ASL, 39 and MRS. 40, 41 This is not guaranteed, however; a recent meta-analysis of 9 studies found that monoparametric and multiparametric MRI performed equally in a clinical context. 42 Another caveat is that true versus pseudoprogression is a false dichotomy as oftentimes there is an intermixing of viable tumor and treatment effect with variable ratios of the two components.…”
Section: Clinical Applications Of Advanced Mrimentioning
confidence: 99%
“…Similarly investigations based on a combination of DSC and DTI data have also categorized tissue into true progression, mixed response, and pseudoprogression. 38 Such approaches may more accurately model post-treatment tumors.…”
Section: Clinical Applications Of Advanced Mrimentioning
confidence: 99%
“…For gliomas, PET and perfusion imaging are important for differentiation. For brain metastases, the data are limited, and progression is defined according to the RANO criteria for brain metastases [12,24,26,27,33,34]. In this study, recurrent tumor was proven histopathologically in 3 of 6 cases with local recurrence.…”
Section: Discussionmentioning
confidence: 99%